Rethinking Vehicle Architecture Through Softwarization and Servitization - Alaa Khamis; Partha Goswami (IEEE Access)
The automotive industry is undergoing a foundational transformation driven by software-defined vehicles (SDVs), where software not only orchestrates vehicle functionality but also redefines the value proposition through servitization, making services a key differentiator rather than the physical product. This paper explores the industry’s shift from a hardware-centric paradigm to one defined by software and presents a comprehensive review of SDVs, structured around a systematic analysis of scientific publications and patents. It lays out the evolution from a distributed to a centralized compute architecture and discusses the promises of SDVs and their challenges. In particular, the paper highlights critical obstacles including fragmented certification frameworks, lack of standardized toolchains, limited support for continuous validation, and rising complexity in software maintenance and repair. Additional concerns include vulnerability management, long-term software support, supply chain decentralization, regulatory compliance, and the absence of open datasets, simulators, and benchmarking tools. The software-centric nature of SDVs also imposes new demands on hardware scalability and future-proofing. Finally, we highlight future directions and research opportunities such as ecosystem collaboration, open innovation, open and standardized datasets, open education simulators and testbeds, quantifiable Quality of Experience (QoX), cognitive data sampling, and contextual observability. This work offers a structured and forward-looking perspective on how SDVs are fundamentally reshaping automotive technology and business models toward intelligent, service-centric mobility ecosystems. To fully realize this potential, several technical, operational, regulatory, and organizational challenges must be addressed across the SDV lifecycle.